O transporte escolar de estudantes da zona rural: dificuldades e desafios enfrentados no percurso - JESUS, Cintia Bispo de (Universidade Federal do Tocantins, 2021)
The present study focuses on the difficulties that rural students face during their journey to school, in this perspective, we sought to find out if the service offered by public agencies meets the demand of the regions and what needs to improve with regard to the school transport in the countryside. Thus, as a general objective we intended to analyze the quality of school transport, and whether this transport really meets the region's demand. A theoretical study was carried out with authors addressing this topic, such as Caldart (2012), Arroyo (1999), Valadão (2018), Costa (2008), among others. The methodology addressed in this study is a qualitative research, which took place through the application of questionnaires to some students and teachers, an interview with some drivers and a direct observation in school transport. As a result, it was found that students still face numerous difficulties in getting to school, and that several issues regarding transportation need to be improved.